Pelatihan Penyusunan Artikel Ilmiah Bagi Mahasiswa IIM Surakarta - Izzun Khoirun Nissa; Sulistyowati; Moch Taufik Nur SW (Scimadly Publishing, 2023)
Writing a scientific article is an important step in preparing for a quality final assignment. A good scientific article not only describes research clearly and systematically, but also shows its relevance and contribution to the chosen field. Therefore, students are required to understand the concepts in preparing scientific articles. This workshop aims to provide the understanding and skills needed in writing scientific articles, appropriate structure, and techniques in the article writing process. The method in this PKM includes presentation, practice and discussion sessions. Participants were introduced to the steps in writing a scientific article including selecting the article title, identifying questions, reviewing the topic, preparing a framework for thinking, collecting data, analyzing data and discussing the results. Apart from that, participants will be taught how to avoid plagiarism and comply with the code of ethics in scientific writing. It is hoped that the results of this workshop will be able to provide knowledge and in-depth understanding about writing scientific articles that are suitable for publication in reputable journals.